Risk Factors of Low Birth Weight in Pakistan - Sana Iqbal, Awais Tanveer, Zarmast Khan, Khawaja Muhammad Junaid, Nazia Mushtaq, Nazish Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Birth weight is a reliable and sensitive indicator of a new-born’s chances of long-term survival, growth, and physical and psychosocial development. There is little research in Pakistan that documents valuable data such as detailed maternal consumption data and psychological factors and links them to low birth weight. The aim was to estimate the LBW proportion and to assess the factors influencing birth weight. Methods: This cross-sectional study was held in the community medicine department in collaboration with Obstetrics and Gynecology department of Jinnah hospital, Lahore and Darul Sehat Hospital, Karachi for the duration of four months from February 2021 to July 2021. A total of 130 patients were selected in consecutive samples, and then a questionnaire was given to them. Results: Among 130 women, the LBW frequency was 16.9%, and the mean birth weight was 2.7 ± 0.6 kg. We also found a significant relationship between birth weight and per capita income, maternal weight gain during pregnancy, number of prenatal visits, maternal education, tobacco use and nutritional stress, and egg consumption. Multivariate analysis showed a significant relationship between maternal weight gain and birth weight during pregnancy, tobacco use, and stress. Conclusion: More people were found to have access to basic prenatal care measures such as nutrition, free iron supplements, and regular prenatal checks, indicating a positive effect on birth weight in the study population. While several factors have been shown to be related to each other, the focus should be on psychological and nutritional factors.